التداخل التطبيقي بين القياس والمصلحة المرسلة والاستحسان: دراسة تحليلية مقارنة - حسين، فرحت (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Qiyas (juristic analogy), Maṣlaḥah mursalah (unrestricted public interest) and Istihsan (juristic preference) are considered important principles among the adillah taba'iyyah (dependent evidences) for ruling on new issues that are subject to ijtihad (juristic reasoning). Although majority of scholars agreed that from the evidential viewpoint Qiyas is stronger than Maṣlaḥah mursalah and Istihsan, disagreement occurred among the schools of Islamic law on whether maṣlaḥah mursalah and Istihsan can be considered as evidences of Shari'ah or not. Meanwhile, the forms of interference emerge between these three evidences, which results lack of clarity in disagreement between scholars and disorder in terms of evidences. However, the scope for further research and review on the issue is still there. At this very juncture, this research focuses on gathering scholars' opinions from schools of Islamic law regarding the interference between Qiyas, maṣlaḥah mursalah and Istihsan, studying them in order to understand the views and interpretations. Besides, this is an analytical and comparative study for explaining the interference between these three evidences, in terms of their theories and practical applications. The researcher has used inductive, analytical and comparative approaches in order to achieve the objectives of this study. The major findings of the study include the proof of theoretical interference between Qiyas and Maṣlaḥah mursalah which is shown in considering maṣlaḥah mursalah as an evidence for deriving ruling of the Shari'ah under Qiyas and in specifying the general rulings by maṣlaḥah mursalah. The proof of theoretical interference between Qiyas and Istihsan is shown in al-Qiyas al-khafī (hidden analogy) and in Istihsan which specifies the general rulings of Qiyas. The proof of theoretical interference between maṣlaḥah mursalah and Istihsan is shown in Istihsan al-maṣlaḥah (juristic preference based on public interest) and in comparison of scholars' standings and opinions regarding them. The applications for interference are shown in classical and new examples, as well as the impact of disagreement on interference is discussed with classical and new examples from branches of Islamic jurisprudence. Thus, the study concludes explaining the importance of adjustment for these terms and rectification of scholar's stands towards them based on the interference found in this research.